The role of serum Pseudomonas aeruginosa antibodies in the diagnosis and follow-up of cystic fibrosis - Doğru, Deniz; Pekcan, Sevgi; Yalçın, Ebru; Özçelik, Uğur; Kiper, Nural; Gürcan, Nermin; Şener, Burçin (The Turkish Journal of Pediatrics, 2013)
In cystic fibrosis (CF), if Pseudomonas aeruginosa (Pa) infection is not diagnosed and treated early, chronic colonization occurs, which causes rapid decline in pulmonary functions. The aim of this study was to evaluate Pa antibodies, compare them with Pa cultures and determine their role in early diagnosis and follow-up. Ninety CF patients were included; they were divided into chronic, intermittent, negative, and mucoid groups. They were evaluated every 3-6 months. In each visit, pulmonary function tests and sputum cultures were obtained, and Pa antibodies exotoxin A (ExoA), elastase (ELA) and alkaline protease (AP) were determined in the serum by enzyme-linked immunosorbent assay (ELISA). The most specific test that discriminated chronic colonized patients from noncolonized patients was Pa culture, and the presence of at least one antibody had the highest sensitivity. AP had the highest specificity, and ELA had the highest sensitivity. All antibodies were highest in the mucoid group. ELA was highest in chronic and lowest in the negative group. The presence of antibodies was much higher than positive Pa cultures in patients younger than five years of age. A negative correlation between forced expiratory volume in 1 second (FEV1) and AP was determined only in the mucoid group. In the two-year follow-up, antibody presence did not show a regular pattern. In CF, Pa antibodies can be early markers for diagnosis, especially in young children who cannot expectorate, but they should only be used together with sputum cultures for long-term follow-up and treatment.